Rapid and convenient detection of SARS-CoV-2 using a colorimetric triple-target reverse transcription loop-mediated isothermal amplification method - Yang, Zhu; Liu, Nicole Y.; Zhu, Zhiwei; Xiao, Minmin; Zhong, Shuzhi; Xue, Qiqi; Nie, Lina; Zhao, Jinhong (PeerJ, 2022)
Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2 poses a significant threat to global public health. Early detection with reliable, fast, and simple assays is crucial to contain the spread of SARS-CoV-2. The real-time reverse transcription-polymerase chain reaction (RT-PCR) assay is currently the gold standard for SARS-CoV-2 detection; however, the reverse transcription loop-mediated isothermal amplification method (RT-LAMP) assay may allow for faster, simpler and cheaper screening of SARS-CoV-2. In this study, the triple-target RT-LAMP assay was first established to simultaneously detect three different target regions (ORF1ab, N and E genes) of SARS-CoV-2. The results revealed that the developed triplex RT-LAMP assay was able to detect down to 11 copies of SARS-CoV-2 RNA per 25 µL reaction, with greater sensitivity than singleplex or duplex RT-LAMP assays. Moreover, two different indicators, hydroxy naphthol blue (HNB) and cresol red, were studied in the colorimetric RT-LAMP assay; our results suggest that both indicators are suitable for RT-LAMP reactions with an obvious color change. In conclusion, our developed triplex colorimetric RT-LAMP assay may be useful for the screening of COVID-19 cases in limited-resource areas.
Keywords: SARS-CoV-2; RT-LAMP; Triple target; Colorimetric